14C AND OTHER RADIONUCLIDES IN THE ENVIRONMENT IN THE BORDER REGION OF LITHUANIA BEFORE THE START OF THE BELARUSIAN NUCLEAR POWER PLANT OPERATION. Issue 6 (19th April 2022) - Mažeika, Jonas; Jefanova, Olga; Petrošius, Rimantas; Lujanienė, Galina; Skuratovič, Žana
ABSTRACT: In this paper, we analyze the background activity of anthropogenic radionuclides ( 14 C, 3 H, 137 Cs, and 239, 240 Pu), emphasizing 14 C content, in terrestrial and aquatic ecosystems in the Lithuanian border region before the commissioning of a new nuclear power plant in Belarus (BelNPP). In terrestrial samples, the 14 C concentration varied insignificantly—from 98.6 ± 0.7 to 102.2 ± 0.8 pMC, which is close to the 14 C level in atmospheric CO2 . In aquatic samples, the 14 C concentration varied within wide limits from 76.9 ± 0.7 to 99.6 ± 0.6 pMC, depending on the ecological group of macrophytes. Various ecological groups of macrophytes have experienced the influence of a freshwater reservoir effect. This lowest 14 C content in submerged macrophyte species, within the limits of uncertainty, was very close to the specific activity of 14 C in DIC (78.6 ± 0.6 pMC) in the water of the Neris River. The background 14 C values, together with the data on 3 H, 137 Cs and 239, 240 Pu obtained in this study, can be used in the future to assess the contribution of the BelNPP conventional radioactive effluents to the levels of 14 C and other radionuclides in terrestrial and aquatic ecosystems of the transboundary region of Belarus and Lithuania.